Produktivitas Primer dan Komunitas Plankton Di Danau Buatan Kawasan Pemukiman Ogan Permata Indah Jakabaring Palembang - Rohayati, Tati; Hilda, Hilda; Husnah, Husnah (Faculty Fisheries Departement Fisheries, 2003)
Study on primary productivity and plankton community of man-made lake situated at Organ Permata Indah, Jakabaring area, Palembang was conducted in October and November 2002. Study was carried out by stratified random sampling and laboratory analysis. Samples for primary productivity, planktonÂ and water quality were taken from several sampling sites set up by using stratification method. Statification was based on the depth of the lakes which were station A (370 to 450 cm), station B (330-350 cm) and station C (200 to 240 cm). The result showed that primary productivity in October and November 2002, reached 3,75 and 12,51 mg C/m3/hour, respectively. The average abundance of phytoplankton was 595,56 and 1383,34 ind/L respectively. Composition of phytoplankton consisted of 71 genera, deriving from five classes: Cyanophyceae, Chlorophyceae, Bacillariophyceae, Xanthophyceae and Chrysophyceae. Genus which had high abundance where Chroococcus and Synechococcus (Cyanophyceae), Bracteococcus, Chlorella, Gonatozygon and Pleurotaenium (Chlorophyceae). Extreme low pH, high transparency and daily oxygen cycle indicated that OPI can be categorized as an oligotrophic lake.Keywords : man-madelake, acidity, productivity, plankton